Autosomal dominant SCN8A mutation with an unusually mild phenotype. (September 2016) - Anand, G.; Collett-White, F.; Orsini, A.; Thomas, S.; Jayapal, S.; Trump, N.; Zaiwalla, Z.; Jayawant, S.
Abstract: Background: Mutations in SCN8A, coding for the voltage-gated sodium channel Nav 1.6, have been described in relation to infantile onset epilepsy with developmental delay and cognitive impairment, in particular early onset epileptic encephalopathy (EIEE) type 13. Case report: Here we report an infant and his father with early onset focal epileptic seizures but without cognitive or neurological impairment in whom next generation sequence analysis identified a heterozygous mutation (c.5630A > G, p. (Asn1877Ser)) in the SCN8A gene. This mutation, confirmed by Sanger sequence analysis, affects a highly conserved amino acid and in silico tools predicts that it may be pathogenic. The reported infant has a normal developmental profile at 16-month follow-up. His father also had normal development and has no cognitive impairment at 42 years. This is the second known SCN8A mutation associated with a phenotype of benign familial infantile epilepsy. Good seizure control was achieved in our patients with sodium channel blockers. Conclusion: Based on our proband and a recently described group of families with benign familial infantile epilepsy and SCN8A variant we suggest expanding testing to patients with infantile epilepsy and no cognitive impairment. In addition, the same SCN8A variant (c.5630A > G, p. (Asn1877Ser)) is also found in patients with epilepsy and developmental delay highlighting the phenotypic variability and the possible role of other protective genetic factors. Highlights: Mutations in the gene SCN8A mutation, affecting the Nav 1.6 voltage-gated sodium channel, are typically associated with early onset epilepsy with developmental delay and cognitive impairment. We describe a proband and his father with a heterozygous familial mutation (c.5630A > G, p.(Asn1877Ser)) in the SCN8A gene which in silico analysis suggests may be pathogenic. The proband and his father have infantile epilepsy with no cognitive impairment. Good seizure control was achieved with sodium channel blockers, particularly phenytoin and carbamazepine. This is the second reported familial SCN8A mutation with infantile epilepsy and no developmental delay, previously associated with a more severe phenotype.